KAJIAN TERHADAP PEMIKIRAN ISMAIL RAJI AL-FARUQI TENTANG ISLAMISASI SAINS - Nanda Septiana (JIE (Journal of Islamic Education), 2020)
Al Faruqi argued that modern (western) knowledge gave rise to a conflict of revelation and reason among Muslims. Separating thought from action, as well as the existence of cultural and religious dualism. Therefore, Al Faruqi believes that the Islamization of Science is needed and that the effort starts from monotheism. This means that Islamic knowledge always emphasizes the unity of the universe, the unity of truth and knowledge and the unity of life. The idea of ​​islamization, thus, is an attempt to deconstruct Western science and then be reconstructed into the Islamic knowledge system. The idea of ​​islamization of science is more comprehensive and clear and has a decent place for discussion.